Wellbeing versus Sustainable Development – Conceptual Framework and Application Challenges - Dłużewska, Anna (Problemy Ekorozwoju, 2017)
The idea of sustainable development introduced the strong connection between human wellbeing and the state of natural environment. In the Millennium Ecosystem Assessment (MA) perspective, wellbeing is correlated with sustainable development and with ecosystem services, both seen as inextricable elements of one global process, necessary to lead properly Our common future. An important consequence of MA is the necessity for wellbeing strategies to be implemented by governments of many countries, including member states of the European Union. In spite of appearances, this is not an easy task not as much with regard to the difficulties in application (obvious for every type of activity) as with regard to the specific mess in defining what wellbeing is. The aim of this paper is to contribute to wellbeing and sustainability research by presenting a relational conceptualization of wellbeing. The paper is divided into three sections. The author begins with the presentation of wellbeing conceptual background, including Gross National product (GDP), Human Development Index (HDI), Genuine Progress Indicator (GPI) monetary valuation, Concept of Capabilities, Societal Indicators, QoL and ecosystems wellbeing theory. The second section focuses on subjective wellbeing conceptual framework, including hedonic and eudaimonic accounts, the Self Determination Theory, the Theory of Subjective Wellbeing Homeostasis and finally the Responsible Wellbeing one. The third section discuss how wellbeing is presented in official directives and policies such a Millennium Ecosystem Assessment 5 dimensions valuation and its implementations in different countries.